2022
DOI: 10.3389/fphar.2021.791889
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC01134 Contributes to Radioresistance in Hepatocellular Carcinoma by Regulating DNA Damage Response via MAPK Signaling Pathway

Abstract: Hepatocellular carcinoma (HCC) is a highly mortal cancer that could be treated by radiotherapy. DNA damage response (DDR) is a vital factor affecting cancer development after radiotherapy. Long non-coding RNAs (lncRNAs) have been revealed to regulate DNA damage response and repair in cancer cells. Nevertheless, the function of long intergenic non-protein coding RNA 1134 (LINC01134) has not been explored in DDR. In this study, we targeted digging into the function of LINC01134 in DDR and exploring the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Previous studies have shown that LINC01134 was highly expressed in CHOL, COAD, LAML, LIHC [7,8,19], PRAD and READ tissues compared with corresponding normal tissues (Figure S1A). Thus, further analysis was conducted to identify the correlation between LINC01134 and colorectal cancer (CRC) via the online tool GEPIA (http://gepia.cancer-pku.cn/detail.php) [15].…”
Section: Linc01134 Is Upregulated In Crc and Correlated With A Poor P...mentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies have shown that LINC01134 was highly expressed in CHOL, COAD, LAML, LIHC [7,8,19], PRAD and READ tissues compared with corresponding normal tissues (Figure S1A). Thus, further analysis was conducted to identify the correlation between LINC01134 and colorectal cancer (CRC) via the online tool GEPIA (http://gepia.cancer-pku.cn/detail.php) [15].…”
Section: Linc01134 Is Upregulated In Crc and Correlated With A Poor P...mentioning
confidence: 81%
“…Recently, LINC01134, a novel lncRNA, was attached to increasing importance in cancers, especially in hepatocellular carcinoma (HCC). It was veri ed that LINC01134 promoted the progression of HCC through facilitating tumors proliferation, migration, epithelial-mesenchymal transition, oxaliplatin resistance, and radioresistance [7][8][9][10]. However, the possible roles and mechanisms of LINC01134 in the occurrence and development of CRC are still largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…LINC01133 has been shown to play an important role in the occurrence and development of gastric ( 43 ), epithelial ovarian ( 44 ), cervical ( 45 ), and pancreatic cancers ( 46 ). LINC01134 has been proven to be relevant to immune response and metabolism in hepatocellular carcinoma (HCC) and has also been identified as an effective biomarker for HCC treatment ( 47 , 48 ). Furthermore, MHENCR has been found to be a predictor of poor prognosis in CRC patients and a regulator of tumourigenesis through the inhibition of miR-532-p ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been implicated in processes such as epithelial-mesenchymal transition (EMT) ( 42 ), immune cell infiltration (specifically T cell migration) ( 52 ), and resistance to chemotherapy and radiotherapy ( 49 51 ) in HCC ( Table 1 ). Furthermore, LINC01134 plays a regulatory role in HCC development by influencing key signaling pathways, including the Nuclear Factor Kappa B (NF-κB) inflammatory pathway ( 43 ), the MAPK signaling cascade ( 50 ), and the tumor suppressor p53 pathway ( 45 ), as well as genes involved in tumorigenesis and disease progression ( Table 1 ). These insights are instrumental in comprehending the essential role of LINC01134 in the functional landscape of HCC.…”
Section: Linc01134 and Hccmentioning
confidence: 99%